A new species of the Chinese endemic genus Sinhomidia (Collembola: Entomobryinae) described and the first description of amale of Sinhomidia bicolor - Jin, Han; Jia, Shao-Bo; Yan, Hua-Chao; Jordana, Rafael (Zootaxa, 2017)
We describe the male of Sinhomidia bicolor for the first time noting a morphological difference from the female. A new species, Sinhomidia guangxiensis sp. nov. is described and illustrated. The new species differs from S. bicolor by the appendages lacking scales, the mucronal basal spine reaching the apex of subapical tooth, the number of chaetae on the trochanteral organ and the distribution of macrochaetae on Th. II, Abd I and Abd II. A key to Sinhomidia species and a diagnostic table to separate male and female S. bicolor and the new species are provided.